Gas exchange and contents of carbohydrates and nitrogen compounds in physic nut irrigated with saline water and wastewater - Sousa, Antonio Evami Cavalcanti; Silveira, Joaquim Albenisio Gomes; Gheyi, Hans Raj; Lima Neto, Milton Costa; Lacerda, Claudivan Feitosa de; Soares, Frederico Antonio Loureiro (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the changes in gas exchange and in the contents of carbohydrates and nitrogen compounds in physic nut (Jatropha curcas) irrigated with wastewater and saline water. The experiment was carried out in a randomized block design, with four treatments and four replicates: irrigation with tap water at 0.6 dS m-1 (control); full irrigation with saline tap water at 2.4 dS m-1 (Salt); and irrigation with wastewater at full (W100) or at 50% field capacity (W50). The W50 treatment remarkably reduced gas exchange and leaf area in comparison to the control, followed by Salt and W100 treatments. Reduction in photosynthesis lowered leaf‑sucrose content in the four treatments. Total soluble sugar contents increased in W50, Salt, and W100 treatments, while starch content remained almost unaltered. Proline and glycine betaine contents increased in these treatments, but the latter was quantitatively more important as osmotic and cellular protector. Full irrigation with wastewater induces similar effects to the ones caused by irrigation with saline water. Irrigation with limited amounts of wastewater caused an acute stress to plants, probably due to a combination of water deficit and solute accumulation in the soil.